Does increasing the organic fertilizer application rate always boost the antibiotic resistance level in agricultural soils?. (1st April 2023) - Guo, Yajie; Qiu, Tianlei; Gao, Min; Ru, Shuhua; Gao, Haoze; Wang, Xuming
Abstract: The amendment of organic fertilizer derived from livestock manure or biosolids is a significant driver of increasing antibiotic resistance in agricultural soils; however, it remains unclear whether increasing organic fertilizer application rates consistently enhances soil antibiotic resistance levels. Herein, we collected soils with long-term amendment with three types of organic fertilizers at four application rates (15, 30, 45, and 60 t/ha/y) and found that the higher the fertilization rate, the higher the antibiotic resistance gene (ARG) abundance. However, when the fertilization rate exceeded 45 t/ha/y, the ARG abundance ceased to significantly increase. Moreover, the soil ARG abundance was positively correlated with total nitrogen (TN) content and bacterial abundance, especially Firmicutes, and negatively affected by pH and bacterial diversity. Soil TN/bacterial abundance and pH/bacterial diversity reached maximum and minimum values at the 45 t/ha/y fertilization rate, respectively. Meanwhile, at this fertilization rate, Firmicutes enrichment peaked. Therefore, an organic fertilization rate of 45 t/ha/y appeared to represent the threshold for soil antibiotic resistance in this study. The underlying mechanism for this threshold was closely related to soil TN, pH, bacterial abundance, and diversity. Taken together, the findings of this study advance the current understanding regarding the soil resistome under different fertilization rates, while also providing novel insights into organic fertilizer management in agricultural practices. Graphical abstract: Image 1 Highlights: Organic fertilization rate of 45 t/ha/y is soil antibiotic resistance threshold. Resistance threshold is related to soil TN, pH, bacterial abundance/diversity. Soil ARG abundance positively correlates with TN and bacterial abundance. Soil ARG abundance negatively correlates with pH and bacterial diversity. Firmicutes abundance peaks at a 45 t/ha/y fertilization rate.